Issue related to vegetation characterization and mapping using fieldwork, G.I.S. and remote sensing high resolution data - Casalegno S. (Comprehensive economic and spatial bio-energy modelling, 2002)
Integrating remotely sensed high resolution data, Digital Elevation Model, agro-ecological data and fieldwork using G.I.S can help in estimating biomass yield. The present paper shows how vegetation mapping and characterization carried out in Southern Baja California, can be used as an example to propose some wider applicable principles and procedures. General problems related to fieldwork and to the acquisition and analysis of satellite images are also discussed.
Seminar on Comprehensive Economic and Spatial Bio-Energy Modelling, 2001/06/07-08, Grignon (France)